(untitled) (Academia Journal of Medicine, 2025)
Aim: This study aims to investigate and compare the occurrence of dentinal fractures during root canal preparation using a scanning electron microscope (SEM). Materials and Methods: Thirty extracted human mandibular premolars were divided into three groups of ten: two experimental groups and one control group. In the experimental groups, root canals were shaped using Group I: the Waldent Walflex file and Group II: the Trunatomy (TRN) file. Group III served as the control group with no canal preparation. After sectioning the roots at 3, 6, and 9 mm from the apex, the surfaces were analyzed using SEM. Results: Data were analyzed using the Chi-square test. The untreated control group (Group III) showed no signs of cracks. Dentinal cracks were primarily observed in the Waldent Walflex group, particularly between the 3 mm and 6 mm intervals. Conclusion: The study highlights that dentinal cracks are more pronounced with the Waldent Walflex file. These findings underscore the need for careful selection of endodontic instruments to minimize the risk of dentinal defects during root canal procedures. Further research is warranted to explore the long-term implications of these findings on treatment outcomes.